Determinants of full-service carriers choices in aviation industry of Thailand - Anaspree Chaiwan (2018)
© Serials Publications Pvt. Ltd. This study applied the classifier chain maximum entropy (CC-GME) method to examine factors determining consumers' choices of full-service carriers (FSCs) in Thailand's aviation market. The CC-GME method developed to explain multi-label choice behaviors is suitable for this study because each consumer generally chooses to travel with more than one carrier each year. The carrier choice determinants include not only consumers' demographics, but also consumers' scores on the importance of each carrier attribute toward their choices. The results show that consumers' demographics did not affect the carrier choices as much as the importance scores on carrier attributes. The carrier attribute with the highest impact was the airfares for Thai airways, Malaysia Airlines, and Bangkok Airways. In addition, the results also show that consumers who traveled with Thai Airways were more likely to also travel with Bangkok Airways and Malaysia Airlines than with other FSCs. The significance of the airfare indicates price competition and the dependence pattern of carrier choices indicates substitutability among FSCs.